2004
DOI: 10.1016/j.bbadis.2004.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deficiency inhibits primary tumor growth but favors metastasis in mice

Abstract: The results of several experimental and epidemiological studies have shown an inverse correlation between Mg status and the risk of some cancers. However, relationship between magnesium and cancer is complex. The aim of our work was to examine the precise effect of Mg deficiency on transplantable mouse tumor growth and metastasis. The results obtained indicate a significant retardation of primary tumor growth (up to 70%) in mice receiving Mg-deficient diet. However, Mg repletion caused in these mice significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 15 publications
3
53
0
Order By: Relevance
“…It is presumed that these antitumor activities of DSW may be derived from the combined ionic action of several minerals such as calcium, magnesium and potassium in DSW. Among these minerals, calcium and magnesium may play important roles in mediating the inhibition of metastasis because they are the main mineral ions present in DSW and it was found that deficiency of magnesium and/or calcium levels has been linked to increased risks of cancer and metastasis (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…It is presumed that these antitumor activities of DSW may be derived from the combined ionic action of several minerals such as calcium, magnesium and potassium in DSW. Among these minerals, calcium and magnesium may play important roles in mediating the inhibition of metastasis because they are the main mineral ions present in DSW and it was found that deficiency of magnesium and/or calcium levels has been linked to increased risks of cancer and metastasis (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…whether Mg deficiency impacts on tumour growth in vivo, a study showed that dietary Mg deprivation inhibited tumour growth in rats by limiting glutathione (GSH) synthesis (Mills et al, 1986), for which Mg is an obligatory cofactor. More recently, in mice subcutaneously injected with Lewis lung carcinoma, mammary adeno--carcinoma and colon carcinoma cells, a low Mg--containing diet was shown to inhibit primary tumour growth, an effect that was promptly reversed by re--introducing Mg in the diet (Nasulewicz et al, 2004). Surprisingly, Mg deficient mice developed far more lung metastases than controls.…”
Section: Magnesium and Cancer: More Questions Than Answers Introductionmentioning
confidence: 99%
“…An elevation in free Mg 2+ concentration in capillary endothelial cells increases the proliferation of endothelial cells, restores the cell's ability to generate and utilize ATP for cellular repair mechanisms, and improves disrupted BBB integrity in a variety of insults. In addition to the stimulatory effect of Mg 2+ on endothelial cell migration and proliferation, the observation that high Mg 2+ concentration facilitates the re--endothelialization of vascular injuries may also provide new insights into the role of Mg 2+ in angiogenesis (Maier et al, 2004). A decrease in Mg 2+ level in the microcirculation of the cortical structures causes a rapid and progressive damage to microvessels, leading to focal haemorrhages and brain edema (Altura et al, 1991).…”
Section: ; Euser and Cipolla 2009mentioning
confidence: 99%
See 2 more Smart Citations